Single-Dose Infliximab in Hepatitis C Genotype 1 Treatmentnaive Patients with High Serum Levels of Tumour Necrosis Factor-Alpha Does Not Influence the Efficacy of Pegylated Interferon Alpha-2B/Ribavirin Therapy - Curtis Cooper; Stephen Shafran; Susan Greenbloom; Robert Enns; John Farley; Nir Hilzenrat; Kurt Williams; Magdy Elkashab; Nabil Abadir; Manuela Neuman (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Serum tumour necrosis factor-alpha (TNF-α) levels correlate negatively with hepatitis C virus (HCV) antiviral response.